HETEROGENEOUS LITHOSPHERIC STRUCTURE OF THE FENNOSCANDIAN SHIELD: SEISMIC DATA - N. V. Sharov; A. A. Lebedev (Геодинамика и тектонофизика, 2022)
A generalization has been obtained based on the data for deep seismic studies on longitudinal DSS profiles (explosion seismology) and seismological evidence found for local and distant earthquakes (earthquake seismology) in the Fennoscandian Shield over the past 40 years. This provided an opportunity to obtaine quantitative data on the horizontal and vertical heterogeneities of the lithosphere. 3D seismological models were first constructed for the individual parts of the Fennoscandian Shield which show that the crystalline crust structure acquires a block hierarchy pattern, with no persistent seismic boundaries found within the entire shield. The upper crust is characterized by the local occurrence of both waveguides and high-velocity zones correlated with geological bodies. The structural plans of the velocity isolines of various deep sections were found to be inconsistent. It has been proved that major geotectonic provinces have a thick crust and that the Early Proterozoic volcanogenic belts are characterized by elevated velocities and a large crustal thickness. In the upper mantle of the Fennoscandian Shield there were identified the layers with anomalously high velocities. No robust evidence was found for a waveguide, which is sometimes related to the concept of the lithosphere.